Literature Review : Audit Internal 5.0: Mengarungi Era Digital Dengan Tranformasi Berbasis Kecerdasan Buatan dan Internet Of Things - Ahmad Arwani; Popi Farahdila Sandi; Dien Noviany Rahmatika (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to identify the role of internal auditors, accountability, transparency, and how technology can be used to improve the effectiveness, benefits and risks of internal audits. The extent to which technology changes, artificial intelligence, and the tools offered by these technologies will impact the future of internal audit. This research method uses qualitative data collection methods, using literature observations carried out by researchers and practitioners. This research was carried out using the LR (Literature Review) method, which was carried out in several stages: First, the author researched journals using keywords such as 'Digital Technology', 'Artificial Intelligence', 'Internet of Things'. “Internal Control” and “Internal Audit” The author has conducted research using electronic databases such as Google Scholar, Semantic Scholar, Scopus, Publish Or Perish, Scispace and many other websites. This research is an important tool that provides information about technological changes and technical intelligence that are critical to the future of the audit profession and offers various suggestions for improving the efficiency and effectiveness of audit professionals' work. Therefore, this study suggests future research to investigate changes and increase knowledge.